Research on the Evolutionary Decision-Making Behavior Among the Government, Farmers, and Consumers: Based on the Quality and Safety of Agricultural Products - Yun Teng; Xinlin Chen; Zhigang Yu; Jingbo Wei (IEEE Access, 2021)
The primary factors that impact food safety are the quality and safety of agricultural products. The quality and safety of agricultural products are closely related to farmers’ decision-making behavior. In addition, the decision-making behavior of the government and consumers is the key factor of farmers’ decision-making behavior. The study explores the ideal state among the government, farmers and consumers to promote the improvement of the quality of agricultural products, thereby contributing to food safety. The study includes the government, farmers and consumers in an evolutionary game model to explore game relationships and evolution paths of decision making among the three stakeholders. The dynamic analysis of the decision replication, the stability analysis of strategy evolution, and the numerical simulation experiment verify the following: the evolutionary process of the decision-making behavior of the three stakeholders to an ideal state is affected by many factors, and the value ranges of the different factors have different impacts on the convergence speed of the three stakeholders to an ideal state; When certain conditions are met, the decision-making behaviors of the three stakeholders can evolve to an ideal state, and effective government supervision can promote the transformation of farmers from nongreen to green pesticide application behavior, and encourage consumers to purchase high-quality agricultural products.